2018
DOI: 10.25035/ijare.11.01.08
|View full text |Cite
|
Sign up to set email alerts
|

A Cause to Action: Learning to Develop a Culturally Responsive/Relevant Approach to 21st Century Water Safety Messaging through Collaborative Partnerships

Abstract: Globally, and in the United States, drowning is considered a "neglected public health threat" (WHO, 2014b). Reports have shown that there are groups of people in certain communities who are at greater risk. African Americans, as a group, have a drowning death rate 9% higher than that of the overall population, with the greatest disparity being among African American youth (Gilchrist & Parker, 2014). While many national programs and organizations present water safety awareness and drowning prevention efforts wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This is reinforced by Willcox-Pidgeon et al [ 53 ] who found that adults often miss out on swimming lessons, which generally prioritise children, and by Moran and Wilcox [ 43 ] who reported that many new migrant adults do not consider swimming and water safety important for themselves but do prioritise swimming lessons for their children. The results of this study, therefore, support the call to action outlined by Scarr et al [ 23 ] to promote the benefits of learning swimming and water safety skills amongst multicultural communities and to assess the effectiveness of such programs [ 38 , 41 , 53 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is reinforced by Willcox-Pidgeon et al [ 53 ] who found that adults often miss out on swimming lessons, which generally prioritise children, and by Moran and Wilcox [ 43 ] who reported that many new migrant adults do not consider swimming and water safety important for themselves but do prioritise swimming lessons for their children. The results of this study, therefore, support the call to action outlined by Scarr et al [ 23 ] to promote the benefits of learning swimming and water safety skills amongst multicultural communities and to assess the effectiveness of such programs [ 38 , 41 , 53 ].…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that children of migrants are at increased risk of drowning compared to those of Australian-born parents as migrant parents are less likely to be aware of water safety issues, be able to swim and have CPR training [ 39 , 40 ]. Other barriers to swimming participation include resources, affordability and modesty [ 41 , 42 ]. Lack of proficient swimming education and lesser swimming ability amongst people from multicultural communities may contribute to their high-risk status in beach environments [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, aquatic spaces in the United States have been the site of discriminatory policies resulting in inequitable access to these areas for members of diverse demographic groups both racially (Dawson, 2018; Waller & Bemiller, 2018) and socioeconomically (Beale-Tawfeeq et al, 2018; Waller & Norwood, 2009). These historical inequities have led to contemporary aquatic management techniques that have largely focused their diversity-related efforts on reactive measures rather than the proactive expansion of inclusion.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In the United States, racial disparities in drowning rates persist even after controlling for socioeconomic status [ 4 ]. Lack of familiarity, lack of access, fear of drowning, and the cost of attending swimming lessons and activities are barriers to learning swimming and water safety among under-resourced and CLED communities [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, studies have shown that disparities are often systemic in nature, based on public health approaches and public policies [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recreational aquatic sites have been the setting for the turmoil of social justice, water safety, and public health in the past. With CLED communities continually lacking access and having limited to no water safety education and/or drowning prevention programming, it is essential when engaging CLED communities, with policies and safety messages, that attempts be made to ensure policies and educational experiences work for all [ 3 , 4 , 5 , 6 , 7 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%